2010
DOI: 10.1007/s15010-010-0001-8
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-resistant Staphylococcus aureus (MRSA) in Europe: which infection control measures are taken?

Abstract: The data obtained regarding MRSA prevention measures should stimulate infection control professionals to pursue further initiatives. Particularly, the vigorous MRSA management in countries with decreasing MRSA proportions should encourage hospitals to implement preventive measures in order to reduce the spread of MRSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…For example, Hansen et al report a ratio of 8 single-patient rooms over 10 in French participating ICUs to a European survey on MRSA infection control measures. 28 We believe this ratio is consistent with the 70% adherence rate of French responders in our survey regarding the availability of single-patient rooms. Figures are similarly consistent between the two studies for other countries like Spain or Germany.…”
Section: Strength and Limitations Of The Studysupporting
confidence: 87%
“…For example, Hansen et al report a ratio of 8 single-patient rooms over 10 in French participating ICUs to a European survey on MRSA infection control measures. 28 We believe this ratio is consistent with the 70% adherence rate of French responders in our survey regarding the availability of single-patient rooms. Figures are similarly consistent between the two studies for other countries like Spain or Germany.…”
Section: Strength and Limitations Of The Studysupporting
confidence: 87%
“…Substantial variation in MRSA control measures between European countries has been described [22]. Our study shows that the implemented control measures also differ considerably between ICUs within one country.…”
Section: Discussionmentioning
confidence: 69%
“…The vast majority reported a policy for contact/isolationprecautions for culture-positive patients, which is congruent with other studies that reported high use of barrier/isolation precautions for infected patients. 12,18,21 The presence of other MDRO-related infection control policies in our sample was low and may reflect wide variation in published recommendations on these interventions or their interpretation.…”
Section: Discussionmentioning
confidence: 91%